Modeling doxorubicin-induced-cardiotoxicity through breast cancer patient specific iPSC-derived heart organoid - Jiye Jang; Hyewon Jung; Jaekyun Jeong; Junseok Jeon; Kyungho Lee; Hye Ryoun Jang; Jeung-Whan Han; Jaecheol Lee (Heliyon)
Heart organoid (HO) technology has successfully overcome the limitations of two-dimensional (2D) disease modeling and drug testing, thereby emerging as a valuable tool in drug discovery for assessing toxicity and efficacy. However, its ability to distinguish drug responses among individuals remain unclear, which is crucial for developing predictive models. We addressed this gap by comparing human induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CMs) with human induced pluripotent stem cell-derived heart organoids (hiPSC-HOs) in the context of doxorubicin-induced cardiotoxicity (DIC). For this study, we utilized hiPSCs generated from breast cancer patients who had previously been treated with doxorubicin. By comparing groups with and without DIC, we examined various parameters, including cell viability, mRNA expression, protein expression and electrophysiological variations. The results of our analysis revealed significant differences between these groups, providing insights into hiPSC-HOs as a potential platform for testing differences in drug responses among patients.